miRNAs and lncRNAs: Potential Non-Invasive Biomarkers for Endometriosis - Ioana Maria Maier; Adrian Cornel Maier (Biomedicines, 2021)
Many studies have tried to understand the mechanism of endometriosis and its manner of manifestation. However, the only method of diagnosis considered as the gold standard in endometriosis is an invasive method called exploratory laparoscopy. Hence, there is a need to identify non-invasive or minimally invasive methods to minimize patients’ suffering, thus increasing their addressability at the earliest possible staging of the disease, and to diagnose this condition as soon as possible. miRNAs (microRNAs) and lncRNAs (long-noncoding RNAs) are potential non-invasive diagnostic methods for endometriosis. Multiple clinical trials indicate that miRNA can be used as a non-invasive method in the diagnosis and differentiation of endometriosis stages.